The Influence of Polyanions and Polycations on Bacteriophage Activity - Musin, Egor V.; Kim, Aleksandr L.; Dubrovskii, Alexey V.; Kudryashova, Ekaterina B.; Ariskina, Elena V.; Tikhonenko, Sergey A. (Polymers, 2021)
Phage therapy is a great alternative to antibiotic drugs, but it can’t effectively overcome the over-acidic medium of the stomach. We offer the use of polyelectrolyte microcapsules as a protective means of bacteriophage. It is necessary to understand the influence of polyelectrolytes on bacteriophage survival. The work studied the effect of polyanions and polycations on the coliprotetic bacteriophage’s viability. We have shown that polyallylamine decreased bacteriophage’s viability during increasing polyelectrolyte concentration and polyarginine had a lower inhibitory effect (then PAH) on the activity of the bacteriophage due to polyelectrolyte concentration from 0.05 to 5 mg/mL. It was shown that the inhibition of the bacteriophage by polyallylamine had an electrostatic nature and the use of high ionic strength prevented the formation of the PAH-protein capsid complex. Polystyrene sulfonate does not affect bacteriophage viability during increasing polyelectrolyte concentration from 0.05 mg/mL to 1 mg/mL. Polystyrene sulfonate decreases the viability of bacteriophage from 5 mg/mL of polyelectrolyte concentration. Dextran sulfate inhibits bacteriophage activity at 20–30%. Dextran inhibits bacteriophage activity by 80% at diapason concentration from 0.05 to 5 mg/mL and loses the inhibition effect from a concentration of 5 mg/mL.